Systematic Literature Review of Barriers to Teachers’ Professional and Digital Competence in Developing Contexts (2020–2025) - Siti Yulaikhah; Suhendra; Rita Retnowati; Nandang Hidayat (Journal Informatic, Education and Management (JIEM), 2026)
This systematic literature review (SLR) examines the barriers hindering the development of teachers’ professional and digital competence in developing countries between 2020 and 2025. The study integrates findings from 30 peer-reviewed journal articles indexed in Scopus, Web of Science, and Google Scholar. Using the PRISMA 2020 framework, the review identifies five major categories of barriers: (1) individual factors (motivation, self-efficacy, and digital anxiety), (2) institutional and organizational constraints, (3) infrastructural and technological limitations, (4) policy and governance barriers, and (5) socio-cultural and contextual factors. The results reveal that teachers in developing regions face interrelated structural and psychological obstacles that limit their capacity to integrate digital technologies and sustain professional growth. The paper concludes with a conceptual synthesis outlining the need for holistic, context-aware professional development programs and equitable digital access policies.